1985
DOI: 10.1111/j.1365-2621.1985.tb13776.x
|View full text |Cite
|
Sign up to set email alerts
|

Contents and Retention of Nutrients in Extra Lean, Lean and Regular Ground Beef

Abstract: Contents and retention of nutrients in raw and cooked (broiled, roasted and grilled to medium-well stage) ground beef patties were established. Fat levels of the raw patties were 18.4, 21.5, and 27.0%. Cooking yields were slightly lower and energy contents were higher for patties containing 27.0% fat than 18.4 or 21.5%. Total lipids, energy content, thiamin and pantothenic acid were the least retained nutrients while zinc was the highest. Generally, retentions after broiling or grilling were the same but were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
26
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 16 publications
6
26
1
2
Order By: Relevance
“…Gerber, Scheeder, and Wenk (2009) have shown considerable fat losses in several meat cuts submitted to grilling, broiling or pan-frying without fat added. Specifically regarding fatty acid composition, an increase in polyunsaturated/saturated ratio was observed, as also reported by Ono et al (Ono, Berry, & Paroczay, 1985) probably because polyunsaturated fatty acids are part of the cell membrane and thus have less contact with the heat.…”
Section: Fat Contentsupporting
confidence: 63%
“…Gerber, Scheeder, and Wenk (2009) have shown considerable fat losses in several meat cuts submitted to grilling, broiling or pan-frying without fat added. Specifically regarding fatty acid composition, an increase in polyunsaturated/saturated ratio was observed, as also reported by Ono et al (Ono, Berry, & Paroczay, 1985) probably because polyunsaturated fatty acids are part of the cell membrane and thus have less contact with the heat.…”
Section: Fat Contentsupporting
confidence: 63%
“…Modifications of fatty acids during cooking could be related to 3 mechanisms: oxidation, loss of fatty acids by diffusion (in roasting) or fatty acid exchange between chicken and oil (in grilling). Ono et al [10] et al [11] in beef patties found a significant decrease of total SFA and an increase of total PUFA with cooking. These authors stated that unsaturated fatty acids were less affected by cooking because they belonged to the membrane structure to a higher extent than saturated fatty acids, leading to a lower decrease of PUFA by diffusion during cooking.…”
Section: Effect Of Cookingmentioning
confidence: 97%
“…Atualmente não existe estatística segura sobre o consumo anual de charque no Brasil, mas estima-se que esteja em torno de 600 mil toneladas [9]. O Regulamento de Inspeção Industrial e Sanitária de Produtos de Origem Animal -RIISPOA determina que o charque deva conter no máximo 45% de umidade e não mais que 15% de cinzas, com variação tolerada de 5% [6].O processamento artesanal deste produto manteve-se praticamente inalterado por muitos anos, até que houve o surgimento do jerked beef, produto cárneo similar, produzido a partir de matéria-prima de qualidade superior e injeção automática de salmoura contendo nitrito e nitrato de sódio, além de ser embalado a vácuo [30].Estudos mostram que procedimentos culinários envolvem transferência de calor e massa, além de reações químicas e físicas que podem causar profundas alterações na composição química dos alimentos [20,23,25] e no perfil de ácidos graxos [1,5,17,20,21]. A importância de uma maior compreensão destes fenômenos e suas repercussões pode não só garantir alimentos de qualidade superior, mas também gerar subsídios para otimizar o processamento dos mesmos [14].…”
unclassified
“…Estudos mostram que procedimentos culinários envolvem transferência de calor e massa, além de reações químicas e físicas que podem causar profundas alterações na composição química dos alimentos [20,23,25] e no perfil de ácidos graxos [1,5,17,20,21]. A importância de uma maior compreensão destes fenômenos e suas repercussões pode não só garantir alimentos de qualidade superior, mas também gerar subsídios para otimizar o processamento dos mesmos [14].…”
unclassified